2021
DOI: 10.4103/jfmpc.jfmpc_332_21
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of under nutrition among under 5 tribal children in a rural area in West Bengal

Abstract: Tribal population is socio economically disadvantaged group. Knowledge about nutritional status of various tribal populations is important because it impels to identify under nutrition which is a leading cause of morbidity and mortality. This study is conducted to assess under nutrition among under 5 tribal children. In this cross sectional study with a sample of 68 under 5 tribal children selected through complete enumeration fulfilling the inclusion criteria after obtaining ethical clearance from Institution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
(7 reference statements)
0
0
0
Order By: Relevance
“…Use of quantitative ethnobotanical tools for analyzing collected data is becoming very much crucial now a day to add more objectivity to this field of research (Leonti et al, 2002;Hoffman and Gallaher, 2007;Rahaman, 2017). Perusal of literature revealed that a large portion of the tribal community including Santals living in the laterite region of West Bengal uses wild edibles in their daily diet (Bandyopadhyay and Mukherjee, 2009;Roy et al, 2015) but still suffer from malnutrition mainly due to lack of optimum amount of food intake and other socio-cultural limitations (Bisai, 2014;Stiller et al, 2020;Chandra et al, 2021). On the other hand, with ongoing anthropogenic activity in the forest, shifting cultivation, reliance on the limited number of high-yielding crop varieties, climate change, and changes in socioeconomic conditions of the ethnic people, the traditional societies are silently losing their traditional food heritage along with the related phyto-resources (Łuczaj et al, 2012;Downs et al, 2020;Ghosh-Jerath et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Use of quantitative ethnobotanical tools for analyzing collected data is becoming very much crucial now a day to add more objectivity to this field of research (Leonti et al, 2002;Hoffman and Gallaher, 2007;Rahaman, 2017). Perusal of literature revealed that a large portion of the tribal community including Santals living in the laterite region of West Bengal uses wild edibles in their daily diet (Bandyopadhyay and Mukherjee, 2009;Roy et al, 2015) but still suffer from malnutrition mainly due to lack of optimum amount of food intake and other socio-cultural limitations (Bisai, 2014;Stiller et al, 2020;Chandra et al, 2021). On the other hand, with ongoing anthropogenic activity in the forest, shifting cultivation, reliance on the limited number of high-yielding crop varieties, climate change, and changes in socioeconomic conditions of the ethnic people, the traditional societies are silently losing their traditional food heritage along with the related phyto-resources (Łuczaj et al, 2012;Downs et al, 2020;Ghosh-Jerath et al, 2021).…”
Section: Introductionmentioning
confidence: 99%